2007
DOI: 10.1063/1.2709885
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-vapor and liquid-liquid interfaces in Ising fluids: An integral equation approach

Abstract: The microscopic structure and thermodynamic properties of liquid-vapor and liquid-liquid interfaces in Ising fluids are studied using an integral equation approach. The calculations are performed in the absence and presence of an external magnetic field by solving the corresponding set of Lovett-Mou-Buff-Wertheim integrodifferential equations for the one-particle density distribution functions. The two-particle inhomogeneous direct correlation functions are consistently constructed by nonlinear interpolation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Whereas in general this interaction can be long-range, the common practice is to restrict it to several neighbors. In spite of the model simplicity, the obtained results demonstrate that the Ising fluids possess features qualitatively similar to those of real dipolar magnetic fluids. In addition, one can mention the successful application of the Ising model to the description of the solid magnetic materials.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Whereas in general this interaction can be long-range, the common practice is to restrict it to several neighbors. In spite of the model simplicity, the obtained results demonstrate that the Ising fluids possess features qualitatively similar to those of real dipolar magnetic fluids. In addition, one can mention the successful application of the Ising model to the description of the solid magnetic materials.…”
Section: Introductionmentioning
confidence: 76%
“…The magnetic dipole–dipole interaction that determines the behavior of magnetic fluids is long-range and depends on the orientation of the intermolecular axis with respect to the direction of the magnetic moments, ranging from attractive (tail-to-tail orientation of the dipoles) to repulsive (side-by-side orientation). To simplify the problem, the so-called Ising fluid in which the interaction between the magnetic moments of the fluid molecules does not depend on the orientation of the intermolecular axis and involves only one component of the magnetic moment can be considered. Whereas in general this interaction can be long-range, the common practice is to restrict it to several neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…17 In a previous work, the RISM theory has also been extended to deal with the interfacial liquid in a theory named the Ornstein-Zernike/Lovett-Mou-Buff-Wertheim (OZ/LMBW) theory. [77][78][79][80] During the development of this theory, it was suggested that the LMBW hierarchy may be more suitable than the YBG hierarchy when there are association effects like the hydrogen bonding on the liquid interfaces. However, for large hydrophobic surfaces, the LCW theory 17 has already been proven to be successful in capturing the water density depletion at the solute-solvent interface by minimizing the solvation free energy with respect to the reference liquid density.…”
Section: The Solvation Free Energy For Solute With Various Hydrophmentioning
confidence: 99%